A new 4-D chaotic system with self-excited two-wing attractor, its dynamical analysis and circuit realization - Mustafa, M.; Sambas, A.; Vaidyanathan, S.; Zhang, S.; Mujiarto, .; Subiyanto, .; Sanjaya, W.S.M. (2019)
A new four-dimensional chaotic system with only two quadratic nonlinearities is proposed in this paper. It is interesting that the new chaotic system exhibits a two-wing strange attractor. The dynamical properties of the new chaotic system are described in terms of phase portraits, equilibrium points, Lyapunov exponents, Kaplan-Yorke dimension, dissipativity, etc. The new chaotic system has two saddle-foci, unstable equilibrium points. Thus, the new chaotic system exhibits self-excited attractor. Also, a detailed analysis of the new chaotic system dynamics has been carried out with bifurcation diagram and Lyapunov exponents. As an engineering application, an electronic circuit realization of the new chaotic system is designed via MultiSIM to confirm the feasibility of the theoretical 4-D chaotic model.